Good, quarrelsome, bad: animal agency and human-elephant interactions in the Western Ghats, India - Bhat Dundi, Deepak; Praet, Istvan; Marvin, Garry (Frontiers in Conservation Science, 2023)
Ecological breakdowns are posing many serious threats to the lives of both humans and wild animals in the spaces where those lives are shared. Today the intensification of conservation-related conflict is one of the main ecological challenges faced in the Western Ghats of India. This Article explores some of the complex interactions between different groups of people, such as wealthy farmers, small-scale farmers, and Adivasi (indigenous) people, and Asian elephants and suggests potentially non-conflictual approaches to sharing spaces with these elephants. The study used a multispecies ethnographic approach as a primary research method and focused on detailed stories and anecdotes narrated by inhabitants of the study area who had long experience of living with these elephants and who frequently encountered them. Based on insights offered by the stories and anecdotes, the Article argues that the lives of elephants and those of people are deeply and intimately interconnected and co-constructed in the study area; such 'naturecultures' of elephants and humans constitute a complex whole. The stories highlight that most people in the study area know that elephants have agency and are intelligent, emotional beings, and can subvert human attempts to control them. According to local people, each individual elephant possesses a distinct personality: some are good, some are quarrelsome, and some are bad. People believe that, just as human beings do, elephants also perceive and respond to individual humans differently; such beliefs, and the stories created out of them, are non-anthropocentric in nature. Overall, this Article explores how understanding, and treating seriously, the concepts, beliefs, and experiences of multidimensional elephant agency can be beneficial for envisioning possible new ways for human-elephant coexistence.